Exploration of the varieties differences on the volatile and non-volatile metabolites of Alpinia galanga and Myristica fragrans utilizing electronic sensing evaluation and untargeted metabolomics analysis - Haijiao Lin; Xiangmin Li; Zengyi Song; Yu Liu; Zijia Li; Qingyun He; Binbin Wei; Ziwen Wang (Food Chemistry: X)
There are differences in flavor, efficacy, and price between the cardamom varieties Alpinia galanga (H) and Myristica fragrans (R). It is crucial to distinguish their bioactivities and metabolites, given their high economic value and dietary frequency. This study determined total phenolic content (TPC), total flavonoid content (TFC), and in vitro/cellular antioxidant activities of R and H. Their volatile/non-volatile metabolites were analyzed via electronic sensing (E-nose, HS-GC–MS/MS) and untargeted metabolomics (UPLC-ESI-QTOF/MSE). Results demonstrated that R exhibited superior antioxidant capacity to H, with both correlating positively with TPC and TFC. A total of 195 non-volatile metabolites were identified and Malabaricone C, alkyl-DHAP, and (R)-Shinanolone were the key components for distinguishing them. E-nose showed W1C, W2W and W5S sensors were more sensitive. Furthermore, 219 kinds of volatile metabolites were identified, among which 14 key differential volatile components were screened out. The study established a theoretical basis for differentiating and characterizing both cardamoms.